Development of Oxidized Polyvinyl Alcohol-Based Nerve Conduits Coupled with the Ciliary Neurotrophic Factor - Porzionato, Andrea (Materials (Basel), 2019)
Functionalized synthetic conduits represent a promising strategy to enhance peripheral nerve regeneration by guiding axon growth while delivering therapeutic neurotrophic factors. In this work, hollow nerve conduits made of polyvinyl alcohol partially oxidized with bromine (OxPVA_Br(2)) and potassium permanganate (OxPVA_KMnO(4)) were investigated for their structural/biological properties and ability to absorb/release the ciliary neurotrophic factor (CNTF). Chemical oxidation enhanced water uptake capacity of the polymer, with maximum swelling index of 60.5% ± 2.5%, 71.3% ± 3.6% and 19.5% ± 4.0% for OxPVA_Br(2), OxPVA_KMnO(4) and PVA, respectively. Accordingly, hydrogel porosity increased from 15.27% ± 1.16% (PVA) to 62.71% ± 8.63% (OxPVA_Br(2)) or 77.50% ± 3.39% (OxPVA_KMnO(4)) after oxidation. Besides proving that oxidized PVA conduits exhibited mechanical resistance and a suture holding ability, they did not exert a cytotoxic effect on SH-SY5Y and Schwann cells and biodegraded over time when subjected to enzymatic digestion, functionalization with CNTF was performed. Interestingly, higher amounts of neurotrophic factor were detected in the lumen of OxPVA_Br(2) (0.22 ± 0.029 µg) and OxPVA_KMnO(4) (0.29 ± 0.033 µg) guides rather than PVA (0.11 ± 0.021 µg) tubular scaffolds. In conclusion, we defined a promising technology to obtain drug delivery conduits based on functionalizable oxidized PVA hydrogels.